KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DENGAN PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA - Septia Wahyuni; Elfi Rahmadhani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This research aims to look at differences in concept comprehension capabilities using the Problem Based Learning model assisted by Geogebra Software compared to conventional learning. This research is a asi research experiment with quantitative approach using non eguivalent group research design. The population in this study is as straight as grade XI MAN 1 Takengon class XI IPA which consists of 3 classes namely XI IPA1, XI IPA2 and XI IPA3. The selection of samples using random sampling resulted in the selection of class XI IPA1 as an experimental class of 26 students and class XI IPA 3 as a control class of 27 students. The instrument used in the form of a test of mathematical understanding ability in the form of a description test. The data analysis used an independent two-sample test, as abnormal data was used by mann-whitney tests. The results showed that differences in understanding students' mathematical concepts through the application of Problem Based Learning learning models assisted by GeoGebra media in Trigonometric materials.